Review on TNSA diagnostics and recent developments at SPARC_LAB. (2019) - Bisesto, Fabrizio; Galletti, Mario; Anania, Maria Pia; Ferrario, Massimo; Pompili, Riccardo; Botton, Mordechai; Schleifer, Elad; Zigler, Arie
Abstract : Interaction between high-intensity lasers with solid targets is the key process in a wide range of novel laser-based particle accelerator schemes, as well as electromagnetic radiation sources. Common to all the processes is the generation of femtosecond pulses of relativistic electrons emitted from the targets as forerunners of the later-time principal products of the interaction scheme. In this paper, some diagnostics employed in laser–solid matter interaction experiments related to electrons, protons, ions, electromagnetic pulses (EMPs) and X-rays are reviewed. Then, we present our experimental study regarding fast electrons and EMPs utilizing a femtosecond-resolution detector previously adopted only in accelerator facilities.